Perceptions Of Muslim Revival. - Alatas, Syed Hussein (Blackwell Publishing., 2007)

(untitled)
While I was preparing for the address that is the basis for this article, the first questions that I raised to myself were: "For whom am I speaking?" and "What am I going to speak about?" I do not want to speak as an academic, as a scholar; it is the scholars who have created the confusion Surrounding the theme I am going to discuss.